Acute and Chronic Effects of Exercise on Continuous Glucose Monitoring Outcomes in Type 2 Diabetes: A Meta-Analysis - Munan, Matthew; Oliveira, Camila L. P.; Marcotte-Chénard, Alexis; Rees, Jordan L.; Prado, Carla M.; Riesco, Eléonor; Boulé, Normand G. (Frontiers in Endocrinology, 2020)
Objective: To examine the acute and chronic effects of structured exercise on glucose outcomes assessed by continuous glucose monitors in adults with type 2 diabetes. Methods: PubMed, Medline, EMBASE were searched up to January 2020 to identify studies prescribing structured exercise interventions with continuous glucose monitoring outcomes in adults with type 2 diabetes. Randomized controlled trials, crossover trials, and studies with pre- and post-designs were eligible. Short-term studies were defined as having exercise interventions lasting ≤2 weeks. Longer-term studies were defined as >2 weeks. Results: A total of 28 studies were included. Of these, 23 studies were short-term exercise interventions. For all short-term studies, the same participants completed a control condition as well as at least one exercise condition. Compared to the control condition, exercise decreased the primary outcome of mean 24-h glucose concentrations in short-term studies (−0.5 mmol/L, [−0.7, −0.3]; p < 0.001). In longer-term studies, mean 24-h glucose was not significantly reduced compared to control (−0.9 mmol/L [−2.2, 0.3], p = 0.14) but was reduced compared to pre-exercise values (−0.5 mmol/L, [−0.7 to −0.2] p < 0.001). The amount of time spent in hyperglycemia and indices of glycemic variability, but not fasting glucose, also improved following short-term exercise. Among the shorter-term studies, subgroup, and regression analyses suggested that the timing of exercise and sex of participants explained some of the heterogeneity among trials. Conclusion: Both acute and chronic exercise can improve 24-h glucose profiles in adults with type 2 diabetes. The timing of exercise and sex of participants are among the factors that may explain part of the heterogeneity in acute glycemic improvements following exercise.